Proceedings of the Forty-Seventh Annual ACM Symposium on Theory of Computing 2015
DOI: 10.1145/2746539.2746572
|View full text |Cite
|
Sign up to set email alerts
|

Exponential Separation of Information and Communication for Boolean Functions

Abstract: We show an exponential gap between communication complexity and information complexity for boolean functions, by giving an explicit example of a partial function with information complexity ≤ O(k), and distributional communication complexity ≥ 2 k . This shows that a communication protocol for a partial boolean function cannot always be compressed to its internal information. By a result of Braverman [3], our gap is the largest possible. By a result of Braverman and Rao [4], our example shows a gap between com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…While the reduction incurs an exponential loss, this loss turns out to be tight [28,29]. We note that the resulting communication protocol always runs in 2 rounds.…”
Section: Information Complexity Vs Communication Complexity Our Nexmentioning
confidence: 94%
See 1 more Smart Citation
“…While the reduction incurs an exponential loss, this loss turns out to be tight [28,29]. We note that the resulting communication protocol always runs in 2 rounds.…”
Section: Information Complexity Vs Communication Complexity Our Nexmentioning
confidence: 94%
“…First and foremost, we would like to understand to what extent interactive computation can be compressed. The recent results of [28,29] show that it is not the case that for all f , IC (f, ε) = Ω (R(f, ε)). Moreover, more recently, it was also shown [30] that it is not the case that IC ext (f, ε) = Ω(R(f, ε))-at least for relations-and there is every reason to believe that it is not the case for functions either.…”
Section: Properties Of the Interactive Information Complexitymentioning
confidence: 99%
“…Jain, Lee and Vishnoi defined the public coin partition bound, and showed that its logarithm is quadratically related to the communication complexity [JLV14]. In addition, Ganor et al introduced the adaptive relative discrepancy [GKR14b]. We study the relation between public coin partition and adaptive relative discrepancy and show the following:…”
Section: Introductionmentioning
confidence: 94%
“…In a recent breakthrough, Ganor et al [GKR14a,GKR14b] gave an example of a function f and a distribution µ, for which there is an exponential separation between the distributional information and communication complexity. Does this settle the question of communication versus information?…”
Section: Introductionmentioning
confidence: 99%
“…But the quantum version of the embedding argument requires new methods. In the classical setting, using classical information cost IC, as soon as we have Alice and Bob privately sample the remaining inputs, the Shearer-type embedding follows almost directly from a Shearer like inequality for information [GKR15]. In the quantum setting, we would similarly like to use a Shearer-type inequality for quantum information [ATYY17].…”
Section: Proof Overviewmentioning
confidence: 99%